Priorities of Health Issues in Periodic Plans of Nepal - Rokaya, Raj Bahadur (Janaprakash Journal of Multidisciplinary Research, 2024)
The concepts of the economic planning in Nepal starts form the Rana regime. Rana prime minister Juddha Samsher makes a concept to apply the program for development. From the initial stage of periodic plans health has given emphasis. The paper aims to overview the health priorities in periodic plans of Nepal. From the review of the literatures and documents it is found that from the First to Fourth Plans, Nepal focused on establishing essential healthcare infrastructure such as health posts and primary healthcare centers. Maternal and child health, alongside the control of communicable diseases, formed core priorities during this phase. The Fifth to Seventh Plans emphasized expanding healthcare services into rural areas through community-based approaches, aiming to improve healthcare access and outcomes across the population. From the Eighth to Tenth Plans, Nepal underwent health sector reforms, decentralizing healthcare services and focusing on universal health coverage. The transition into the Eleventh to Thirteenth Plans aligned with global health goals, emphasizing the reduction of maternal and child mortality, combating infectious diseases like HIV/AIDS, and addressing environmental health concerns such as air pollution. From Fourteenth to Sixteenth Plans, Nepal faces new challenges such as climate change impacts and COVID-19 pandemic and focus to strengthening health infrastructure, enhancing healthcare financing mechanisms, promoting health equity, and integrating mental health services into mainstream healthcare provisions. Every, periodic plans are influenced by the issues. So far, further plans should focus on non-communicable diseases (NCDs), actions to cope with climate change health impacts, health technologies and probable health emergencies.